Pengaruh Kualitas Produk dan Viral Marketing Terhadap Keputusan Pembelian pada Produk Cushion Instaperfect di Yuna Cosmetics - Annisa Khurotul Mayyasari; Yulis Nurul Aini; Asminah Rachmi (Indo Publishing, 2025)
The development of digital marketing in the modern era encourages business actors in the beauty industry to utilize social media as an effective and efficient promotional tool. Instaperfect, as a local cosmetic brand, has experienced increased sales due to the combination of superior product quality and well-targeted viral marketing strategies. This study aims to determine the influence of product quality and viral marketing on the purchase decision of Instaperfect cushion products at Yuna Cosmetics. This research is a quantitative study. Data collection was conducted through the distribution of questionnaires to 84 respondents who had purchased and used the Instaperfect Cushion product. The sampling technique used was purposive sampling, and the analysis tool employed was multiple linear regression with the help of SPSS software.The results of the analysis show that the product quality variable has a t-count > t-table (4.994 > 1.6589), indicating a positive and significant effect on purchase decisions. Similarly, the viral marketing variable also has a t-count > t-table (4.642 > 1.6589), indicating that viral marketing also has a positive and significant effect. The F-test results show that both variables simultaneously have a significant effect on purchase decisions with an F-count > F-table (64.008 > 3.08). The coefficient of determination (R²) is 0.736, meaning that 73.6% of purchase decisions are influenced by the two independent variables, while the remaining 26.4% is influenced by other factors outside the scope of this research. Based on these results, it can be concluded that product quality and viral marketing, both partially and simultaneously, have a significant influence on purchase decisions. Therefore, it is recommended that Instaperfect continue to maintain and improve product quality while also strengthening its viral marketing strategies in order to increase consumer purchase decisions at Yuna Cosmetics.